Carnival Texts Three plays for ensemble performance - MacDonald, James (Intellect, 2011)
Carnival Texts comprises three related dramatic works, all of which have as their point of departure Russian theorist Mikhail Bakhtin's concept of carnival, a literary style designed to subvert dominant assumptions through chaos and humour. Making creative use of post-Brechtian performance theory, these texts blur the distinction between spectator and performer in a fascinating exploration of physical, moral, and cultural upheaval in a postmodern age. Performance theory is crucial to understanding how performance affects collective understanding, and this book will be of interest to a broad range of students of drama and theatre.